Earth at Your Fingertips Socialization: Getting to Know Digital Maps and Google Earth Regarding Lembang Fault Mitigation at SMP Negeri 2 Lembang - Cahyo Hermanto; Deni Sopiyan; Aisah Nur Endah Sari; Rr. Isni Anisah; Khairan Fathan Hubainallah; Rifky Andriansyah Angela; Sutanto Dwi Putra; Ahmad Fauzan Abdurrohman; Willy Radiansyah; Arya Dutha Ramadhan; Muhamad Rendi Mulana; Revansa Zahrandhika; Wildan Kurniawan; Wahyu Alvan (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2026)
Lembang, located near a fault line, demonstrates significant susceptibility, underscoring the need for proactive disaster literacy initiatives. This community service initiative seeks to enhance students' understanding of earthquake disaster mitigation by using digital maps and Google Earth to pinpoint areas, assess potential risks, and formulate disaster risk reduction measures. The implementation technique is a participatory-educational strategy that includes presentations of materials, demonstrations of digital maps, practical exploration of the Lembang Fault area in Google Earth, and interactive conversations. The participants, students from SMP Negeri 2 Lembang, acquired a thorough understanding of fundamental Geographic Information System (GIS) principles, the identification of high-risk areas, and basic visual-spatial analysis simulations. The findings indicate an enhancement in students' understanding of disaster prevention principles and their capacity to analyze digital spatial data. This activity demonstrates that incorporating digital technology into disaster education effectively enhances risk awareness from a school-age perspective.